Tamed Monsters and Human Problems: in Cinema’s ‘Interview with the Vampire’ (1994) - Robinson, P. Stuart (Nordlit, 2019)
What can the taming of the monster reveal about its construction and the potential and limits of change? Modernist, individualist qualities of Western culture and society have shaped the construction and deconstruction of the monster in popular culture in general and film in particular. The idea of an historically emergent human nature and its associated norms is key to the construction of the monster as transgressive. Less obvious but nonetheless apparent is the constraining role this Western construction of human nature continues to play in recent cinematic attempts to approach the monster more closely. These are explored through a consideration of vampire movies within the horror genre, with a focus on Interview with the Vampire (dir. Neil Jordan, 1994), as arguably both influential within and emblematic of a more general trend. The film dismantles the conventional monster figure of the vampire, humanising her by detailing her transposition from a natural, human setting to something otherworldly. Human (read as Western) qualities are reinforced and salvaged from the disturbing ambivalence of conventional monstrosity, as we observe the logic of ‘human’ adaptation to alien conditions. In this way, both the paradoxical model of freedom as conformity to nature and the naturalising reification of contingent social groupings are re-affirmed.